Protótipo de um sistema de documentação em enfermagem no puerpério - Veríssimo, Regina Célia Sales Santos [UNIFESP] (2010)
The objective of this study was to develop a system prototype for the documentation system of nursing care in the post-natal period. This was an applied research study as well as a technological development as it is used in the construction of a system prototype of documentation. In the planning of the software we used a model based on the orientation of objects suggested by Summerville, that united: the understanding and the definition of the context and the ways of using the system, the architectural project of the system, the identification of the principle objectives of the system, the development of the project models, and the specification of the interfaces of the objects. We used a language of SQL (Structured Query Language) for the development of the data collection bank of the system; for the system generator of the data bank we used the MySQL in the 5.0.51 version. The language im of the program php was used. The study was approved by the Research Ethics Committee (CEP) of the Federal University of São Paulo-UNIFESP/ São Paulo Hospital, under the protocol nº 2178/08. The prototype that was developed showed in the results to have obtained the planned requirements, among these: the use of CIPE® version 1.0 as the support code registered for putting into practice nursing care procedures; the search for patients using their basic personal data; the inclusion of patients through the use of the function ―admit patients‖ with the use of the information sheet of personal data of these patients, or additional information that is needed; the entering of data that refer to the initial phase of the nursing practice procedures (collection of data) in the form of information obtained from the physical exam, data from the interview or even additional information; the insertion of data from the data collection bank through the menus rather than from handwritten information; the entrance of a text freely inserted in the model of data collection; the carrying out of phases automatically completed as they are inserted; the presentation of the main axels of CIPE® 1.0 in their order of use, making this phase easier for the user, making possible, although not mandatory, the automatic formation of a text of the progress of the patient starting with the collection of data previously inserted by the user; the creation of reports about the practice of the nursing care procedures. The development of this prototype represents the possibility of registering nursing care procedures through a standardized language favoring the development of nursing care procedures in a more practical manner and making available precise information necessary for decision making.